The effect of repetitive transcranial magnetic stimulation on sleep quality in patients with more than mild depressive mood: a systematic review and meta-analysis - Yu’ang Liu; Silang Huang; Xinxin Zhang; Huangying Liao; Weiguo Liu; Zhi Zhang; Xianhui Qu; Ziwen Wang (Frontiers in Psychiatry)
BackgroundThe purpose of this study was to systematically evaluate the efficacy of repetitive transcranial magnetic stimulation (rTMS) therapy on sleep quality in patients with more than mild depressive mood.MethodsRandomized controlled trials in PubMed, Cochrane Library, Web of Science, Embase, Scopus, and ScienceDirect on rTMS to improve sleep quality in patients with more than mild depressive mood up to September 2023 were searched. A meta-analysis was performed using RevMan 5.4 and Stata 17.0 software.ResultsA total of 11 studies, which involved 548 patients, were included. After rTMS treatment, the effect on sleep quality improvement in patients with more than mild depressive mood was better in the experimental group than in the control group [I2 = 53%, mean difference (MD) = −2.27, 95%CI = −2.97 to −1.57, p < 0.00001]. The results of the subgroup analyses showed that, in terms of stimulation frequency, compared with the 5-Hz and 10-Hz groups, the treatment effect of the 1-Hz group was better (I2 = 32%, MD = −2.69, 95%CI = −3.78 to −1.60, p < 0.00001). In terms of treatment duration, compared with the 2-week and 4-week groups, the group with more than 4 weeks of treatment had better treatment outcomes (I2 = 0%, MD = −2.81, 95%CI = −3.22 to −2.40, p < 0.00001). In terms of whether combination therapy was used or not, compared with the combination therapy group (I2 = 29%, MD = −1.39, 95%CI = −2.30 to −0.48, p = 0.003), the non-combination therapy group had a better treatment effect (I2 = 0%, MD = −2.93, 95%CI = −3.36 to −2.50, p < 0.00001).ConclusionrTMS significantly improves sleep quality in patients with more than mild depression. Subgroup analyses showed that the group using the 1-Hz stimulation frequency, the group with more than 4 weeks of treatment time, and the group with rTMS alone had better efficacy in treating the sleep quality of patients with more than mild depressive mood using rTMS, with the use of combination treatment or not being the main source of heterogeneity.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023467971